PERMASALAHAN KONFLIK ANTARSTAKEHOLDER DALAM IMPLEMENTASI KEBIJAKAN PENGOLAHAN DAN PEMURNIAN MINERAL DI PROVINSI SUMATERA SELATAN - Junita, Rita; Adiah, Masayu (Jurnal Administrative Reform, 2024)
The aim of the research carried out is to analyze dynamic conflicts between stakeholders in the implementation of domestic mineral processing and refining policies in South Sumatra Province. This research is descriptive research using document content analysis and interactive analysis. Primary data comes from purposive purposes. Sampling technique with informants from the Department of Mines and Energy, entrepreneurs, workers, the community. Research data was collected through interview techniques, documentation and observation. The next step uses data source triangulation to determine the validity of the data. The research results show that there is conflict between stakeholders to prevent this policy from being implemented in South Sumatra Province. The conflict process at the interpretation stage is dominated by conflict discourse at the central stage; the organizing stage, characterized by conflict between policy implementers; The implementation stage relates to conflicts between local entrepreneurs and third parties that arise as a result of the company's temporary suspension. Factors that influence conflict include differences in needs between stakeholders; less effective communication; Emotional tension mounting at the time of application for judicial review; Difference in value; Structure with the presence of pressure groups; Past management history and foreign investment. The type of conflict according to the subject is interpersonal conflict between the government, local entrepreneurs and third parties. The substance of the conflict is realistic, with foreign exchange reserves, high investment and infrastructure facilities that do not support constructive conflict output, with negotiations and realized in the form of a policy vision. According to the field of life, this conflict is an economic and political conflict, namely the struggle for mineral resources using power and authority.